Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Hotel The Acacia Anyer Serang-Banten - Setiawan, Rido; Wahyudi, Wahyudi (Jurnal ATAMA, 2023)
The purpose of this study was to determine whether there is an influence of the work environment on employee performance, to determine whether there is an influence of motivation on employee performance, and to determine whether there is an influence of the work environment and motivation simultaneously on employee performance at The Acacia Anyer Hotel Serang-Banten This study uses a quantitative approach. In contrast, the population in this study is 44 employees at The Acacia Anyer Hotel Serang-Banten. In comparison, the sample is saturated with the sampling technique so that the sample is taken entirely from the total population with a sample of 48 employees. The results of this study obtained results in hypothesis 1 there is a significant influence between the work environment on employee performance at The Acacia Anyer Hotel Serang-Banten. Hypothesis 2 there is a significant effect between motivation on employee performance at The Acacia Anyer Hotel Serang-Banten Hypothesis 3 there is an influence between work environment and motivation on employee performance at The Acacia Anyer Hotel Serang-Banten.